Bacterial load, multiple antibiotic-resistance patterns, and cytotoxic effects of coliform and coliform-related bacteria associated with the surface water of dhaka city (Bangladesh Journal of Botany, 2024)
The surface water quality of Dhaka Metropolitan City was studied from June to December 2022, with special attention to coliform bacterial pollution. The aerobic heterotrophic bacteria, total coliform, and fecal coliform were high in Buriganga and Shitalakshya River water compared to other selected water bodies. The physico-chemical parameters of the selected rivers and lakes were unsatisfactory.  A total of 110 isolates were obtained, of which 26 were selected for further study. Twelve Gram-positive isolates belonged to the genera Enterococcus, Micrococcus, Planococcus and Bacillus. Fourteen Gram-negative isolates belonged to the genera Escherichia, Klebsiella, Enterobacter, Alcaligenes, Pseudomonas, Plesiomonas, Aeromonas and Salmonella. Most of the Gram-negative bacteria were multiple antibiotic resistant (MAR). Plesiomonas shigelloides showed the highest MAR (50%). Klebsiella oxytoca (MAR 40%) and E. coli (MAR 30%) showed a positive cytotoxic effect on the non-cancer cell line. Coliform bacteria associated with the surface water of Dhaka City pose a serious health threat to city dwellers. Bangladesh J. Bot. 53(1): 41-48, 2024 (March)